EatxCali keynote speaker: Frank Rijsberman, CEO, CGIAR. The grand challenge of providing healthy diets for 9 billion people - International Center for Tropical Agriculture (2015)
Keynote speaker: Frank Rijsberman, CEO, CGIAR. EATxCali brings together representatives from academic and government institutions, international agencies, businesses, and civil society to rebuild food systems, and ensure that consumers have access to healthy and more sustainably produced food.